Hambatan dan Harapan Pemartabatan Bahasa Indonesia - Mohamad Jazeri; Siti Zumrotul Maulida (Jurusan Tadris Bahasa Indonesia, 2018)
This article aims to explain the phenomena of dignifying the Indonesian language between obstacles from Indonesian people and hopes from people of other countries to learn and use the Indonesian language. Based on my prolong observation, I find that people of Indonesia nowadays are lack of pride and loyalty to use The Indonesian language. On the other hand, the number of foreigners who are interested in learning the Indonesian language is highly rocketed. In our country, we face some phenomena of using The Indonesian language with lack of pride and loyalty. Language pride is the pride of Indonesian people to use Indonesian language pride, while language loyalty is the wish to use and maintain the Indonesian language from interference and extinction. The hopes from outside are the increasing number of foreigners who learn the Indonesian language for many purposes. It is proved by, first, the Indonesian language is now promoted as an official language of ASEAN countries. Second, the Indonesian language is learned in some universities in foreign countries. Third, in line with the strategic position of Indonesia in global communication, politically, economically, and culturally, the need of Indonesian Language Teaching for Foreigner (BIPA) is rapidly increasing.Penelitian ini bertujuan untuk menjelaskan fenomena yang terjadi dalam pemartabatan bahasa Indonesia, yakni hambatan yang terjadi di dalam negeri dan harapan dari luar negeri. Hasil pengamatan menunjukkan bahwa kebanggaan dan loyalitas warga negara Indonesia terhadap bahasa Indonesia masih rendah. Di sisi lain, bangsa lain semakin banyak yang tertarik mempelajari bahasa Indonesia. Hambatan yang dihadapi di dalam negeri adalah kurangnya kebanggaan terhadap bahasa Indonesia dan rendahnya loyalitas terhadap bahasa Indonesia. Kebanggaan terhadap bahasa Indonesia adalah rasa bangga menggunakan bahasa Indonesia. Sementara loyalitas terhadap bahasa Indonesia merupakan keinginan bangsa Indonesia untuk memelihara dan mempertahankan bahasa Indonesia serta mencegahnya dari pengaruh dan interferensi dari bahasa lain. Adapun harapan dari luar negeri adalah semakin tingginya minat orang asing untuk mempelajari bahasa Indonesia dengan berbagai alasan. Hal ini dapat dilihat dari pertama, bahasa Indonesia dipromosikan sebagai bahasa resmi ASEAN. Kedua,bahasa Indonesia dipelajari di beberapa perguruan tinggi di luar negeri. Ketiga, seiring dengan posisi strategis Indonesia di percaturan dunia, secara politik, ekonomi, dan budaya, permintaan layanan Bahasa Indonesia bagi Penutur Asing (BIPA) meningkat dengan cepat.